A SYSTEMATIC LITERATURE REVIEW: DIFFERENTIATED LEARNING IN IMPLEMENTING THE MERDEKA CURRICULUM IN MATHEMATICS EDUCATION - Fajri, Hardian Mei; Marini, Arita; Zakiah, Linda (PD PGMI se Indonesia, 2023)
Differentiated learning is a hot topic in education today. In the Merdeka curriculum, teachers must use differentiated learning in the classroom. Therefore, it is important to understand how differentiated learning is implemented in mathematics subjects. This descriptive qualitative research uses a Systematic Literature Review (SLR) approach. The Systematic Literature Review research procedure refers to eight steps with three main stages: Planning the review, Conducting the review, and Reporting the review. The literature sources of this research used various articles from Google Scholar, Springer, Taylor & Francis, Elsevier, and ScienceDirect. The results show that implementing differentiated learning positively affects students' mathematics academic achievement; besides that, differentiated learning increases self-efficacy, self-confidence, and motivation in learning mathematics, which can support the achievement of mathematics subject objectives. Differentiated learning effectively provides direct learning opportunities tailored to the conditions, learning styles, characters, and deficiencies of students in learning.